2006
DOI: 10.1016/j.jtbi.2005.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of persister formation on bacterial response to dosing

Abstract: Almost all moist surfaces are colonized by microbial biofilms. Biofilms are implicated in cross-contamination of food products, biofouling and various human infections such as dental cavities, ulcerative colitis and chronic respiratory infections. The recalcitrance of biofilms to typical antibiotic and antimicrobial treatments is one focus of current investigations. Neither reaction-diffusion limitation nor heterogeneities in growth-rate explain the observed tolerance. Another hypothesis is that specialized 'p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 29 publications
6
89
0
Order By: Relevance
“…Balaban et al, 2004;Cogan, 2006;Kussell et al, 2005;Roberts & Stewart, 2005;Sufya et al, 2003;Wiuff et al, 2005), that is, that persisters are cells with the same genome but with different sets of genetic expression than 'normal' cells, and that a given cell can switch back and forth between the two states.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balaban et al, 2004;Cogan, 2006;Kussell et al, 2005;Roberts & Stewart, 2005;Sufya et al, 2003;Wiuff et al, 2005), that is, that persisters are cells with the same genome but with different sets of genetic expression than 'normal' cells, and that a given cell can switch back and forth between the two states.…”
Section: Discussionmentioning
confidence: 99%
“…Balaban et al (2004), Roberts & Stewart (2005) and Cogan (2006) have proposed models in which cells are able to switch in and out of a protected, slow-or non-growing persister state with probabilities that are dependent possibly on environmental conditions. In this paper, based on observations of microbial senescence (Ackermann et al, 2003;Barker & Walmsley, 1999;Mortimer & Johnston, 1959;Stewart et al, 2005), we instead propose an alternative simple mechanism that can explain all of the above-mentioned properties.…”
Section: Persisters Have a Number Of Interesting Characteristicsmentioning
confidence: 99%
“…Biofilm bacteria may produce persister cells that neither grow nor die in the presence of antibiotics (Cogan 2006). Persister cells are largely responsible for the high levels of tolerance to antibiotics seen in biofilms (Lewis 2005), but the environmental stimuli that turn on the switch to the persister phenotype are poorly understood.…”
Section: Small-colony Variants (Scvs)mentioning
confidence: 99%
“…In these regions, although normal cells are unable to grow, they slowly switch to the persister phenotype. Cogan (2006) suggested that expression of persister cells is controlled by the growth rate and the antibiotic concentration. Persister cells can be regarded as specialized survivor cells.…”
Section: Small-colony Variants (Scvs)mentioning
confidence: 99%
“…Many of these mechanisms depend on whether the bacteria exist in a biofilm or not [8,10,13,9]. In particular, the notion that small sub-populations of bacteria may display innate tolerance to various biocides has been proposed as a possible reason for the failure of treatment for bacterial infections [16,2,14,5]. Bacteria within a biofilm are enmeshed in a physical gel that provides a secondary boundary that may allow small numbers of bacteria to evade the antibiotic; therefore, the failure to eliminate the entire population can allow the population to regrow.…”
Section: Introductionmentioning
confidence: 99%